Bringing Record Clearing to You: Feedback and Lessons Learned From Community-Based Record-Clearing Clinics in Philadelphia Neighborhoods - DeYoung, Lena L. (Criminal justice policy review, 2025)
Individuals with a criminal record often face significant barriers to opportunities, including those related to employment, housing, and education. Although options for criminal record clearing exist, few eligible individuals take advantage of these pathways to relief, as relevant information can be difficult to access, and the processes can be considerably costly. Aiming to expand the pursuit of record relief in Philadelphia, a local nonprofit, in partnership with City Council, has been sponsoring neighborhood events where individuals can meet with legal organizations, for free, in their own communities to learn about their records and the forms of relief for which they may be eligible. Then, eligible individuals can choose to partner with the participating legal organization to pursue record clearing in the forms of sealing, expungement, and/or pardon. Researchers attended the initial three clinic events to evaluate operations—through interviews with attendees, feedback from community-based organizations and legal staff, and structured observations—and provided rapid qualitative feedback. Lessons learned from these clinics, including those related to event advertising and access, event experience, and legal clinic experience were shared and leveraged to maximize ongoing clinic programming.